Implementing citizen science activities for climate action: the I-CHANGE Day - Esbrí, Laura; Llasat-Botija, Montserrat; Llasat, Maria Carmen; Sola, Yolanda; Loglisci, Nicola; Brattich, Erika; Racionero, Sandra; Steeneveld, Gert-Jan; Mölter, Anna; Galizia, Antonella; Polo, Lara; Peerlings, Esther E. M.; et al. (Frontiers in Environmental Science, 2025)
The H2020 I-CHANGE project (Individual Change of HAbits Needed for Green European transition) aims to actively engage citizens in tackling climate change through citizen science practices. To this end, I-CHANGE has collaborated with citizens and stakeholders across eight Living Labs (LLs) situated in seven countries representing diverse geographical and climatic regions. This paper presents the I-CHANGE Day, an event organized simultaneously in the eight LLs, with the aim of collecting and analyzing data on air pollution and meteorological variables through citizen science and raise public awareness on climate change and individual adaptation measures. The paper details the methodology adopted to facilitate the citizens’ participation and the implementation of the proposed activities in contrasting social and environmental settings, and the outcomes of these various citizen science activities. The two main activities implemented in the present case study were air pollution monitoring using Smart Citizen Kits (SCKs) and comparing personal temperature and humidity perception with observations acquired through MeteoTrackers sensors. The results show significant community involvement and provide useful insights for enhancing the effectiveness of international citizen science initiatives. They also highlight the importance of a co-creative process to capture different objectives and capabilities of LLs. Across all LLs, the activities presented engaged groups ranging from 8 to 60 citizens, who demonstrated high levels of interest and effectively acquired the skills to operate the low-cost sensors. This study further aims to facilitate the replication of the proposed campaign across other LLs in other areas of the globe.